Podnikatelský plan pro založení krejčovského salonu - Pospíšilová, Marie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Diplomová práce se zabývá zpracováním reálného podnikatelského plánu v oblasti poskytování krejčovských služeb v Letovicích. V práci jsou uvedeny základní teoretické poznatky týkající řešené problematiky. Podnikatelský plán je postaven na výsledcích provedených analýz trhu a konkurence. V části vlastního návrhu je navrhnut podnikatelský plán, který na základě finančního zhodnocení zobrazuje potenciál pro úspěšnost realizace podnikání.

The thesis focusses on presenting a real business plan in the field of dressmaking services in Letovice. The theoretical part of this thesis presents the basic theoretical knowledge of dressmaking itself. The practical part of the thesis focusses on market research. According to an analysis of the marketplace and competition in this area, a business plan proposal has been created. This proposal shows the likely success rate of realization.
Business Plan for the Foundation of the Tailoring Salon
Keywords: podnikatelský plán; krejčovský salón; charakteristika trhu; SLEPT analýza; výroba textilií; finanční plán; business plan; tailoring salon; market charakteristic; SLEPT analysis; manufacture of textiles; financial plan